KERENTANAN SOSIAL DAN EKONOMI PADA BENCANA BANJIR DI KELURAHAN SUTOJAYAN KABUPATEN BLITAR - Yulis Bigandata; Purbudi Wahyuni; Yohana Noradika Maharani (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
Social and economic vulnerability describes the social and economic fragility of an area due to the influence of hazards, threats and disasters that have the potential to damage, disrupt. This study aims to analyze the social and economic vulnerability of the flood disaster in Sutojayan Village, Blitar Regency. Data on social vulnerability is seen from gender, age, rural/urban, education, disability, transportation, and number of households, and economic vulnerability is seen from unemployment and livelihoods. This study uses a mixture of qualitative and quantitative methods with data obtained through interviews of 5 subjects, a questionnaire of 335 people, and documentation using population data of 7048 people. Data analysis techniques to measure social and economic vulnerability using multiple linear regression and SoVI techniques with the help of CFA. The results showed that: (1) The level of social and economic vulnerability in the post-flood disaster was influenced by indicators: gender, age, education, disability, transportation, and livelihood, and (2) The level of social and economic vulnerability in the post-flood disaster was in the high and medium categories. The Sutojayan environment with a SoVi value of 0.229 has a higher level of vulnerability than the Gondang Legi and Purworejo environments, and (3) The dominant variables that affect the level of social and economic vulnerability in the flood disaster are disability, the number of motorized vehicles, and the number of non-motorized vehicles.